Penguatan Paradigma Dakwah dalam Strategi Pemasaran Digital - Korik, Kamdan; A’yun, Alifia Nihayatul (Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has influenced various aspects of life, including Islamic education and preaching. However, the lack of digital literacy among preachers and educators is a major challenge in optimizing social media and digital platforms as a means of preaching and religious marketing. The Digital Education Talkshow for Preaching and Marketing was held in response to this problem. The activity methods include interactive seminars, case studies, and question and answer sessions featuring speakers who are experts in digital preaching and content marketing. The purpose of this activity is to improve participants' competence in integrating preaching strategies and digital marketing techniques effectively. The contribution of the activity can be seen from the increased understanding of participants regarding the use of digital media for preaching and educational promotion. The evaluation results showed that 85% of the 180 participants experienced an increase in their understanding of the concept of digital preaching, and 72% stated that they were ready to implement digital marketing strategies in their preaching activities. This activity proves that an educational and practical approach can be an effective solution to answer the challenges of preaching in the digital era.